Randomized controlled trial to compare the effect of simple distraction interventions on pain and anxiety experienced during conscious surgery. (30th January 2015) - Hudson, B.F.; Ogden, J.; Whiteley, M.S.
Abstract Background High levels of anxiety during surgery are associated with poorer post‐surgical outcomes. This prospective, non‐blinded randomized controlled trial aimed to compare the effectiveness of four intraoperative distraction interventions for anxiety and pain management during minimally invasive venous surgery under local anaesthetic. Methods 407 patients presenting with varicose veins at a private clinic, were randomized to one of four intraoperative distraction interventions or treatment as usual. All participants received endovenous thermoablation and/or phlebectomies of varicose veins. After losses to follow‐up, 398 participants were entered into the analysis. Participants were randomly allocated to one of the following intraoperative distraction techniques: patient selected music (n = 85), patient selected DVD (n = 85), interaction with nurses (n = 81), touch (stress balls) (n = 80) or treatment as usual (TAU, n = 76). The state scale of the STAI, the Short‐form McGill pain questionnaire and numeric rating scales were used to assess intraoperative pain and anxiety. Results Intraoperative anxiety ratings were significantly lower when participants interacted with nurses, used stress balls or watched a DVD during surgery compared to treatment as usual. Intraoperative pain ratings were significantly lower than treatment as usual when participants interacted with nurses or used stress balls during surgery. Patients' satisfaction was not significantly impacted by intraoperative distractions. Conclusions The use of simple intraoperative distraction techniques, particularly interacting with nurses, using stress balls or watching a DVD during surgery conducted under local anaesthetic can significantly improve patients' experiences.